Naturally occurring diversity helps to reveal genes of adaptive importance in legumes - Gentzbittel, Laurent; Andersen, Stig U.; Ben, Cécile; Rickauer, Martina; Stougaard, Jens; Young, Nevin D. (Frontiers in Plant Science, 2015)
Environmental changes challenge plants and drive adaptation to new conditions, suggesting that natural biodiversity may be a source of adaptive alleles acting through phenotypic plasticity and/or micro-evolution. Crosses between accessions differing for a given trait have been the most common way to disentangle genetic and environmental components. Interestingly, such man-made crosses may combine alleles that never meet in nature. Another way to discover adaptive alleles, inspired by evolution, is to survey large ecotype collections and to use association genetics to identify loci of interest. Both of these two genetic approaches are based on the use of biodiversity and may eventually help us in identifying the genes that plants use to respond to challenges such as short-term stresses or those due to global climate change. In legumes, two wild species, Medicago truncatula and Lotus japonicus, plus the cultivated soybean (Glycine max) have been adopted as models for genomic studies. In this review, we will discuss the resources, limitations and future plans for a systematic use of biodiversity resources in model legumes to pinpoint genes of adaptive importance in legumes, and their application in breeding.